IMPLEMENTASI KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) TERHADAP INDIKATOR KERJA UTAMA (IKU) PERGURUAN TINGGI - M. Nursi; Darwianis; Wirnita (Cerdas Proklamator, 2023)
The Independent Campus Learning Policy (ICLP) as stipulated in Kepmendikbud Number 3/M2021 concerning Main Performance Indicators (MPI) of State Universities and Higher Education Service Institutions at the Ministry of Education and Culture and Research and Technology aims to build and implement a collaborative learning system with the liberation of real experiences. From research on the Elementary School Teacher Education Study Program (ESTE), in addition to the implementation not being optimal, the evaluation criteria and scoring formula based on the case method and team base project learning method turned out to be low, there were still many lecturers who used the lecture method, but students' interest in learning with very high collaborative and participatory methods as shown by the learning behavior of students who are so active and participatory in solving problems.Keywords: Implementation, policy, key performance indicators (IKU).